(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT This study compares the numbers of projects and sectors financed by Islamic banks with those financed by their traditional counterparts and compares the returns for Islamic and traditional banks. The focus of this study is on the financing of Islamic banks for service sectors and projects in Iraq, as well as the formulas by which these sectors and projects were financed. In addition, this study examines the financing of Islamic banks for projects and sectors in Iraq. Both the sectors and the projects qualify as institutions of service due to the fact that they provide a service to the receiver, who might be a citizen or a consumer. The study elaborates on projects, as well as the method by which they will be funded, alongside an explanation of their concept, and other pertinent information.